2019
DOI: 10.1073/pnas.1910213116
|View full text |Cite
|
Sign up to set email alerts
|

Piezo2 integrates mechanical and thermal cues in vertebrate mechanoreceptors

Abstract: Tactile information is detected by thermoreceptors and mechanoreceptors in the skin and integrated by the central nervous system to produce the perception of somatosensation. Here we investigate the mechanism by which thermal and mechanical stimuli begin to interact and report that it is achieved by the mechanotransduction apparatus in cutaneous mechanoreceptors. We show that moderate cold potentiates the conversion of mechanical force into excitatory current in all types of mechanoreceptors from mice and tact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 70 publications
2
42
0
Order By: Relevance
“…Previously, we showed that MA could be efficiently enriched in various cell types and, as a consequence, alter the activation profile of PIEZO1 channels by increasing the plasma membrane structural order and rigidity 25 . Interestingly, previous works suggests that PIEZO1 and PIEZO2 have distinct gating mechanisms 30,51 . For instance, Cox et al 28 demonstrated that PIEZO1 is solely gated by bilayer tension in the absence of the cytoskeleton, whereas current evidence suggests that PIEZO2 gating might depend on the cytoskeleton 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that MA could be efficiently enriched in various cell types and, as a consequence, alter the activation profile of PIEZO1 channels by increasing the plasma membrane structural order and rigidity 25 . Interestingly, previous works suggests that PIEZO1 and PIEZO2 have distinct gating mechanisms 30,51 . For instance, Cox et al 28 demonstrated that PIEZO1 is solely gated by bilayer tension in the absence of the cytoskeleton, whereas current evidence suggests that PIEZO2 gating might depend on the cytoskeleton 8 .…”
Section: Discussionmentioning
confidence: 99%
“…2G ). In contrast, Meissner lamellar MA currents decayed significantly faster (τ decay = 11.8 ± 2.3 ms, P < 0.0001 versus Pacinian lamellar MA current), similar to mechanoreceptors with fast and intermediate inactivation kinetics ( 27 31 ), and lacked a persistent, noninactivating component ( Fig. 2, D and G ).…”
Section: Resultsmentioning
confidence: 84%
“…Recently, sphingomyelinase activity has been revealed to be a crucial determinant of Piezo1 inactivation [ 71 ]. Various modulators, such as pH, temperature, divalent ion concentrations, alternative splicing, osmotic swelling, membrane lipid composition, co-expression of other membrane proteins, and G-protein-coupled pathways have also been reported to regulate the Piezo channel kinetics [ 55 , 72 79 ]; however, we still know very little about the relationships among these factors and pivotal structural domains.…”
Section: Kinetics Properties Of Piezo Channelsmentioning
confidence: 99%